Theoretical foundations of the formation of tourist and local lore competencies of students of the Geography educational program - Исаков, Ерлан; Мазбаев, Орденбек; Лайсханов, Шайхислам (Pedagogy and Psychology, 2021)
Professional competencies directly depend on the quality of professional activity of the future specialist and the achievement of the necessary results. Therefore, theoretical works devoted to the study of the problems of the formation of professional competencies are of great importance. In this regard, the article discussed the basics of professional competence in higher educational institutions and the formation of tourist and local lore competencies of students of educational programs of geography, the theoretical foundations of the formation of tourist and local lore competencies on the basis of competencies proposed by domestic and foreign scientists. Also, the possibility of forming tourist and local lore competencies of modern geography educational programs registered in the Register of educational programs was evaluated, and competencies that provide independent knowledge and personal position that contribute to the optimal solution of problems encountered in tourist and local lore were presented.